Cross-sectional study of Filipino consumer perception, attitude, and purchasing patterns across different age groups regarding food packaging material - Castaneda, Carlos Joaquin R.; Basinang, Airisse Rae P. (Quezon City University of the Philippines Diliman, 2025)
Packaging significantly contributes to environmental pollution, driving consumer demand for sustainable product design and highlighting the importance of understanding consumer attitudes and preferences when selecting food packaging materials. The study aimed to assess Filipino consumers’ attitude, perception, and purchasing pattern on food packaging material to identify differences between age groups and identify significant factors affecting consumer purchasing patterns. A structured questionnaire was developed and administered through Google Forms to Filipino consumers (n = 396) from Metro Manila, Philippines to measure consumer attitude, perception, and purchasing patterns in regards to food packaging material. While no significant associations (p > 0.05) were found between consumer attitude items and age groups, respondents generally associated glass with its transparent structure, paper with healthy nature, and plastic with pollution. Significant differences (p < 0.05) in perception, and purchasing patterns were found with older consumers rating glass as higher quality and influence of protective properties for packaging higher than younger consumers. Exploratory Factor Analysis (EFA) extracted three factors that influence purchasing patterns; (1) Functionality and Sustainability, (2) Glass Packaging Perception, and (3) Metal Packaging Perception. Further research on other socio-demographic variables and packaging attributes is recommended for improved understanding.
In partial fulfillment for the Degree of Bachelor of Science in Food Technology
Thesis
Keywords: Food -- Packaging -- Philippines; Consumers -- Attitudes; Package goods industry; Consumer perception; Packaging material; Purchasing patterns